Embracing Modernity: The Evolution of Contemporary Islamic Calligraphy in Indonesia (1979-2014) - Muhamad Maksugi; Asep Achmad Hidayat; Usman Supendi; Ajid Hakim (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to analyze the journey of the acceptance of contemporary Islamic calligraphy in Indonesia from 1979 to 2014. Initially, contemporary calligraphy faced opposition from calligraphers who considered it a violation of Arabic script grammar and often linked it to issues of Islamic jurisprudence concerning halal and haram. The research employs a narrative-analytical historical approach, using data collection techniques such as interviews and exploration of print media. The findings reveal that the acceptance of contemporary Islamic calligraphy in Indonesia involved a lengthy process, beginning with its controversial emergence, conflicts between painters and calligraphers, a phase of revival, and ultimately its acceptance as one of the competition categories in the Mushabaqah Tilawatil Quran (MTQ). This study contributes to a deeper understanding of the dynamics of cultural change and acceptance in the context of Islamic art in Indonesia.